PENGUATAN MODAL USAHA PADA KOMUNITAS PELAKU USAHA KULINER DI KARANGANYAR MELALUI LEMBAGA KEUANGAN MIKRO (LKM) [STRENGTHENING BUSINESS CAPITAL OF CULINARY BUSINESS COMMUNITIES IN KARANGANYAR THROUGH MICRO FINANCIAL INSTITUTIONS (MFIS)] - Ana Shohibul Manshur Al Ahmad; Atmaji Atmaji; Sarjiyanto Sarjiyanto; Sinto Sunaryo (Universitas Pelita Harapan, 2021)
The purpose of this community service is empowerment and efforts to maintain business sustainability in the culinary business community in Cangakan Karanganyar. Partners in this program are the culinary business community in Cangakan, Karanganyar, who have joined the KUBE (Business Community Group) institution. The main problem faced by partners is the aspect of capital, most of the members of KUBE Culinary Cangakan are street culinary traders so that prospective creditors are considered not bankable. In financial terms, this business actually has the potential to develop. The method used to solve the problem is assisting the establishment of a Micro Finance Institution (MFIs), as well as empowering community members through financial management and managerial training. The end result of this program is the formation of a healthy Micro Finance Institution from the culinary business community in Cangakan Karanganyar. Through the established Micro Finance Institution (MFIs), it is hoped that it can be a solution in overcoming working capital problems and business sustainability. BAHASA INDONESIA ABSTRACT: Tujuan pengabdian ini adalah pemberdayaan dan upaya menjaga keberlanjutan usaha pada komunitas pelaku usaha kuliner di Cangakan Karangnyar. Mitra dalam dalam program ini adalah komunitas pelaku usaha kuliner di Cangakan, Karangnyar yang sudah tergabung dalam kelembagaan KUBE (Kelompok Usaha Bersama). Permasalahan utama yang dihadapi oleh Mitra yaitu aspek permodalan, sebagian besar anggota KUBE Kuliner Cangakan adalah pedagang kuliner kaki-lima sehingga dipandang not-bankable oleh calaon kreditur. Secara financial sebetulnya usaha ini memiliki potensi untuk berkembang. Metode yang dipakai untuk menyelesaikan masalah adalah pendampingan pembentukan kelembagaan Lembaga Keuangan Mikro (LKM), sekaligus pemberdayaan anggota komunitas melalui pelatihan manajemen keuangan dan manajerial. Hasil akhir dari program ini adalah terbentuknya Lembaga Keuangan Mikro yang sehat dari komunitas pelaku usaha kuliner di Cangakan Karangnyar. Melalui Lembaga Keuangan Mikro (LKM) yang terbentuk diharapkan dapat menjadi solusi dalam mengatasi permasalahan modal kerja dan keberlanjutan usaha.